Direct determination of kQ for Farmer-type ionization chambers in a clinical scanned carbon ion beam using water calorimetry. (17th February 2017) - Osinga-Blättermann, J-M; Brons, S; Greilich, S; Jäkel, O; Krauss, A
Abstract: Until now, the dosimetry of carbon ions with ionization chambers has not reached the same level of accuracy as that of high-energy photons. This is mainly caused by the approximately threefold larger uncertainty of the k Q factor of ionization chambers, which, due to the lack of experimental data, is still derived by calculations. Measurements of absorbed dose to water, D w, by means of water calorimetry have now been performed in the entrance channel of a scanned 6 cm × 6 cm radiation field of 429 MeV/u carbon ions, allowing the direct calibration of ionization chambers and thus the experimental determination of k Q . Within this work, values for k Q have been determined for the Farmer-type ionization chambers FC65-G and TM30013. A detailed investigation of the radiation field enabled the accurate determination of correction factors needed for both calorimetric and ionometric measurements. Finally, a relative standard measurement uncertainty of 0.8% ( k = 1) could be achieved for the experimental k Q values. For both chambers, the experimental k Q factors were found to be about 1% larger than those tabulated in the German DIN 6801-1 protocol, whereas compared to the theoretical values stated in the TRS-398 protocol, the experimental k Q value agrees within 0.4% for the TM30013 chamber but is about 1% lower in the case of the FC65-G chamber.